Outbreaks and incidence of vector-borne diseases in Colombia (2007-2024): Impact of climate change and deforestation. - Olivera, Mario J.; Porras-Villamil, Julián Felipe; Fuentes, Màrius Vicent (Biomédica: Revista del Instituto Nacional de Salud)
Introduction. Vector-borne diseases pose a public health challenge in Colombia, influenced by climatic and environmental factors. El Niño and deforestation can alter vector habitats, affecting the incidence of dengue, Zika, chikungunya, malaria, cutaneous leishmaniasis, and yellow fever. This study analyzes the relationship between these variables and vector-borne diseases incidence in Colombia (2007-2024). Materials and methods. An ecological study was conducted using incidence and outbreak data for six vector-borne diseases, linked to climate information, El Niño, and deforestation. Regression models and random forests were applied to assess associations. Results. Between 2007 and 2024, 3,283,259 cases of vector-borne diseases were reported in Colombia. Of these, 49.9% (1,639,120) were dengue and 39.8% (1,307,351) malaria, accounting for 89.7% of total cases. El Niño was associated with increased incidence of dengue (β = 213.24; 95% CI: 86.05-338.43), chikungunya (β = 26.41; 95% CI: 17.54-70.36), and Zika (β = 14.12; 95% CI: 10.06-89.30). Maximum temperature showed a positive relationship with dengue (β = 5.74; 95% CI: 2.15-13.63) and malaria (β = 17.28; 95% CI: 3.81-30.75). Deforestation was associated with malaria (β = 12.35; 95% CI: 4.62- 20.08) and cutaneous leishmaniasis (β = 8.67; 95% CI: 2.21-15.13). Mean precipitation had negative associations with chikungunya and leishmaniasis. Conclusions: Climate change and deforestation impact the epidemiology of vector-borne diseases in Colombia. Integrated public health and environmental conservation strategies are needed to mitigate their effects.